IMPLEMENTATION OF A CLOUD-BASED ACCOUNTING INFORMATION SYSTEM TO IMPROVE FINANCIAL TRANSPARENCY OF MSMES IN TANGERANG REGENCY - Sapriyadi; Abu Naim; Purwani Husodo; Annisa Risqi Sulistya Kusuma Wardhani; Siti Fatimatul Zuhro; Rina Ambarwati; Ervina Yennie Permanningrum; Andika Mugi Gumilang; Fery Updi; Adam Zulfahmi (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
The rapid advancement of information technology has significantly influenced the business landscape, including the Micro, Small, and Medium Enterprises (MSME) sector in Tangerang Regency. As key contributors to regional economic growth, MSMEs face the urgent need to adopt digital transformation, particularly in financial management. However, many MSMEs continue to rely on manual or spreadsheet-based systems, which hinder financial transparency, accuracy, and efficiency. This study aims to analyse the implementation of cloud-based accounting information systems (AIS) and their impact on improving MSMEs’ financial transparency in Tangerang Regency. The research employs a quantitative descriptive method, using questionnaires distributed to 100 MSME owners and financial staff who have implemented cloud-based accounting systems. Data were analysed through simple linear regression using SPSS 26 to determine the relationship between the implementation of cloud-based AIS (independent variable) and financial transparency (dependent variable). The results indicate that the implementation of cloud-based AIS has not significantly improved financial transparency among MSMEs in Tangerang Regency, with an R-squared value of 0.003 and a significance level of 0.624 (>0.05). This suggests that only 0.3% of financial transparency variation is explained by the use of cloud-based systems, while 99.7% is influenced by other factors such as digital literacy, infrastructure readiness, and managerial support. Despite the weak statistical correlation, the findings highlight the strategic potential of cloud-based accounting systems to enhance operational efficiency, data accessibility, and stakeholder trust. The study concludes that the success of digital transformation among MSMEs requires not only technological adoption but also government facilitation, training in digital literacy, and policy support to maximise transparency and accountability in financial management.